PENETRATING NECK INJURY EVALUATION AND MANAGEMENT: PENETRATING NECK INJURY - Mukul Yadav; Deepchand; Gaurav Gupta; Vivek Samor; Subhash (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: To study the prevalence of penetrating neck injuries in north-west Rajasthan. Methods: This was a cross-sectional study on 50 patients with penetrating injury to the neck and of either sex fulfilling inclusion and exclusion criteria, who visit our Trauma Centre and ENT OPD at PBM hospital Bikaner during 01 Jan 2022 to 01 Jan 2023. Patients was evaluated and resuscitated as per Advanced Trauma Life Support Protocols. If the patient is stable a multi-detectorcomputed tomography (MDCT) Angiography will be done and treatment was done accordingly. All patients were observed for at least 48 hours prior to discharge. Follow up of all patients was done at 4 weeks and 3 months post discharge. Results: Mean age of study population was 31.53 ± 9.24 yr with age range of 18–70 yr. Maximum 90% caseswere male; 54% cases were urban. 48% cases were in II zone, followed by 24% in III rd zone, 16% in IVth Zone, whereasminimum 12% had injury in multiple zones. conservative treatment was done in 34% cases, 33 cases were treated by surgery out of which 57.57% were treated by surgical debridement and primary wound closure, 88% cases were cured and1(2%) case were died. Conclusion: A proper evaluation, rapid air way intervention and proper surgical repair are essential for a successful outcome. Early management of laryngeal injury within first 24 hours seems to bear the bestresults for air way and voice.